LAND APPROPRIATION IN ILLEGAL PARKING PRACTICES AT ALUN-ALUN KIDUL YOGYAKARTA: A LAND GRABBING PERSPECTIVE FROM DAVID HARVEY’S THEORY - Kresiya Satria Pideksa, Dwi Karsa; Mirza, M Yusril (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2025)
Urban public spaces in Indonesia have increasingly become sites of informal negotiation between human actors and material infrastructures. In cities like Yogyakarta, illegal parking is not merely a regulatory violation but a complex spatial practice reflecting urban contestation. This study builds upon prior research on urban informality, particularly David Harvey’s theory of land grabbing, to examine how public space in Alun-Alun Kidul is informally appropriated and commodified through illegal parking practices. Unlike dominant narratives that frame informal parking solely as disorder or absence of law, this study highlights its embeddedness within socio-material interactions and urban economies. The research aims to uncover how spatial contestation and land grabbing logic operate on a micro scale through daily informal practices in Alun-Alun Kidul, a culturally symbolic and economically strategic public space in Yogyakarta. Employing an ethnographic methodology, the study conducted multi-sited fieldwork involving participant observation, semi-structured interviews, and visual documentation from November to December 2024. It also utilized media reports and urban policy documents to triangulate findings. The study reveals that illegal parking is sustained through tactical use of mundane materials, negotiation with local authorities, and integration into local tourism economies. Informal actors commodify public space through practices that displace pedestrians and marginalize alternative users, reflecting patterns of spatial inequality. These practices align with Harvey’s conception of land grabbing, where space is seized for capital accumulation under informal regimes.